Model updating of a dynamic model of a composite steel-concrete railway viaduct based on experimental tests. (1st June 2018) - Malveiro, Joel; Ribeiro, Diogo; Sousa, Carlos; Calçada, Rui
Highlights: FE model for a railway viaduct is calibrated and experimentally validated. Special attention is paid to the local behaviour of the RC deck slab. Modal damping coefficients are estimated for different vibration levels. The relevance of the horizontal support stiffness is discussed. Abstract: This paper presents a procedure to obtain the physical properties of the finite-element (FE) model of a railway viaduct, suitable for the estimation of the deck slab's dynamic response during the passage of trains. This procedure is based on experimental results and involves two phases. The first phase consists in the calibration, using a genetic algorithm, to calculate the optimal values for the most influential physical properties, which maximise the agreement between the experimental modal parameters and the ones provided by the FE model. The experimental modal parameters are determined through a dynamic test under forced random vibration. The second phase consists in the modification of the value of two physical properties, the horizontal stiffness of the supports and the modal damping coefficients. These properties have to be adjusted as they lead to different dynamic performances of the structure, depending on whether the structure is subjected to low intensity ambient vibration actions, or subjected to high intensity loads during the passage of trains. The adjustment is based on the slab's dynamic response (displacements, strains and accelerations) measured during the passage of real trains.